Numerical analysis of thermal and mechanical stress profile during the extrusion processing of plasticized starch by non-isothermal flow simulation. (April 2021) - Emin, M.A.; Wittek, P.; Schwegler, Y.
Abstract: The non-isothermal, non-Newtonian, transient flow of plasticized starch in a co-rotating twin-screw extruder is simulated by using 3-dimensional (3D) computational fluid dynamics (CFD) accompanied by particle tracking simulation. The results show that the maximum stresses are generated at the tip of the screws. These maxima lead to local hot spots with temperatures up to 10 K higher than material temperature at low shear regions. The particle tracking simulation allowed calculating maximum stress distribution among the extruded material, which vary significantly. The results further suggest that increasing screw speed can lead to lower mechanical stresses due to decreased matrix viscosity. Despite the lower mechanical stresses, increasing screw speed still results in the exposure of material to significantly higher material temperature. Overall, results reveal the significance and the necessity of the in-depth analysis of local extrusion conditions by non-isothermal CFD and particle tracking simulations. Highlights: Non-isothermal transient flow during extrusion was simulated by CFD. Screw rotation can lead to temperature difference up to 10 K at a single barrel location. The results were in accordance with the experimental data measured by an infrared sensor. The thermal and mechanical stress profiles were calculated by particle tracking simulations. Influence of screw speed on thermomechanical stress profile was analyzed.